Sensor and User Interaction-Based Evaluation of Clinical Trials Implemented in a form of a Mobile System Assisting Parkinson’s Disease Treatment - Tomasz GUTOWSKI; Mariusz CHMIELEWSKI (Communications of International Proceedings, 2020)
The paper introduces a novel system for pharmaceuticals companies or medical facilities that support or conduct clinical trials. The system consists of two applications, the CT (clinical trials) management portal accessible only to the supervisor of the trials and a mobile application concentrated on collecting data from the patient. The paper proposes a novel solution which allows to organize and accurately track the efficiency of clinical trials using sensor-based examinations, daily surveying, medicine intake reporting and user interaction tests. This set of activities makes the process of evaluation of the treatment easier and less prone to inaccuracies and subjectivity. The paper focuses on the usage of the system in clinical trials regarding the Parkinson’s disease, testing new medicines and new approaches to the therapy. The paper presents synthetic view of requirements and conceptual and testing phase of a deployed IQPharma Clinical Trials Assistant system. The original findings concern correlating aspects (methods) of pharmaceutical therapy evaluation for Parkinson’s Disease including: Patient subjective health state evaluation - using answers provided in the surveys, Detection of motor symptoms and evaluation of their intensity using signals of inertial and biomedical sensors – aggregated features of actigraphy and electromyography. Reflex and mental perception assessment using user interaction exercises to evaluate the reaction time, accuracy of movement and providing complemental assessment of patient.
Keywords: Parkinson’s Disease; mobile system; clinical trials; patient state evaluation.